A photocatalyst based on mixed phase TiO2 nanomaterials and its preparation method and application
By loading TiO2(B) nanosheets on anatase phase TiO2 nanoribbons, a mixed-phase TiO2 nanomaterial was prepared, which solved the problem of poor dispersion of TiO2(B) in aqueous solution, and achieved efficient photocatalytic degradation effect.
Patent Information
- Application Number
- CN202411115754.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-08-14
AI Technical Summary
TiO2(B) has poor dispersion in aqueous solution and is prone to agglomeration, which limits its application as a photocatalyst.
A mixed-phase TiO2 nanomaterial and anatase phase TiO2 nanoribbons were used as carriers, and TiO2(B) nanosheets were loaded, and prepared by solvothermal reaction.
The dispersion of the material in the aqueous solution is improved, agglomeration is avoided, the photocatalytic efficiency of the material is enhanced, and it can effectively degrade organic dyes, chlorophenol compounds, antibiotics and heavy metal ions in the water.
Smart Images

Figure CN118949963B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalysts, and in particular to a photocatalyst based on mixed-phase TiO2 nanomaterials and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the rapid growth of population and the rapid development of industry, water pollution is becoming more and more serious. These pollutions not only cause serious environmental problems, but also pose a huge threat to people's lives and health. Compared with traditional methods of treating water pollutants, photocatalytic treatment technology has very obvious advantages. Most pollutants can be oxidized or reduced by photocatalytic reactions to generate carbon dioxide and water and other harmless molecules or ions. This treatment method is very friendly to the environment. At the same time, the conditions of photocatalytic reactions are not harsh, and the reaction rate is fast and easy to control. It uses light as a driving force, can utilize inexhaustible solar energy, and is conducive to energy conservation. Therefore, applying photocatalytic technology to the treatment of water pollution is an ideal choice with great development potential.
[0004] Among many photocatalytic semiconductor materials, TiO2 has become the most promising semiconductor photocatalyst due to its strong redox property, stable physical and chemical properties, corrosion resistance, low price and no secondary pollution. TiO2(B) is another TiO2 crystal phase discovered after anatase, rutile and brookite. It is composed of TiO6 octahedrons connected in two ways: edge-sharing and vertex-sharing. There is an open channel between the axial oxygen atoms and parallel to the Y axis. This structure gives TiO2(B) a unique crystal internal anisotropy, which is particularly suitable for charge transfer. Therefore, it was initially often used as a negative electrode material for solar cells. At the same time, studies have found that TiO2(B) is a metastable structure with a large number of surface oxygen defects that can attract photogenerated electrons and serve as reaction sites; and its bandgap width is lower than that of anatase and rutile phases, which is conducive to increasing the range of light absorption; therefore, TiO2(B) has the potential to be a photocatalyst. However, TiO2(B) has poor dispersibility in aqueous solution and is prone to agglomeration, thus limiting its application as a photocatalyst. Summary of the invention
[0005] In order to overcome the above problems, the present invention provides a photocatalyst based on mixed-phase TiO2 nanomaterials and a preparation method and application thereof.
[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0007] The first aspect of the present invention provides a mixed-phase TiO2 nanomaterial, which uses anatase phase TiO2 nanobelts as a carrier and is loaded with TiO2 (B) nanosheets.
[0008] The second aspect of the present invention provides a method for preparing the mixed phase TiO2 nanomaterial, comprising:
[0009] (1) dispersing titanium dioxide P25 in an alkaline solution, and then performing a solvothermal reaction, washing the precipitate after the reaction to obtain a neutral value, obtaining H2TiO3 nanobelts, and calcining to obtain anatase phase TiO2 nanobelts;
[0010] (2) Anatase TiO2 nanobelts are dispersed in a solvent, TiCl4 is added, and then a solvothermal reaction is performed to obtain a mixed phase TiO2 nanomaterial.
[0011] The third aspect of the present invention provides the use of the mixed-phase TiO2 nanomaterial as a photocatalyst in photocatalytic degradation of pollutants.
[0012] The beneficial effects of the present invention are:
[0013] (1) Among the three traditional TiO2 crystal phases, the anatase phase has the most stable properties at the nanoscale and the best photocatalytic performance, so most TiO2-based photocatalysts choose anatase nanostructure. However, the larger band gap (3.2 eV) makes the anatase phase TiO2 only absorb ultraviolet light, which accounts for only 5% of sunlight, and the photogenerated electrons and holes generated by the single crystal phase TiO2 after being photoexcited are very easy to recombine, which will affect the photocatalytic efficiency of the material. The present invention provides a mixed phase TiO2 nanomaterial, which uses anatase phase TiO2 nanobelts as a carrier and is loaded with TiO2 (B) nanosheets. The lower band gap of TiO2 (B) allows the material to absorb part of the visible light, and the defects distributed on its surface can act as electron traps to participate in the photocatalytic reaction. When the mixed phase TiO2 is photoexcited, the photogenerated electrons and holes can migrate between the two crystal phases. At the same time, the introduction of TiO2(B) nanosheets greatly increases the surface area of the material. When the photogenerated carriers migrate to the surface of the material, they can quickly react with the organic molecules in the system, thereby increasing the rate of the photocatalytic reaction while effectively avoiding the recombination of the photogenerated carriers, ensuring that the photocatalytic reaction is stable at a high level for a long time. Furthermore, loading TiO2(B) nanosheets on anatase phase TiO2 nanobelts can improve the dispersion of TiO2(B) nanosheets in aqueous solution and avoid agglomeration. At the same time, the mixed phase TiO2 formed by the combination of the two increases the hydrophilicity of the material surface, thereby improving the photocatalytic efficiency.
[0014] (2) The mixed-phase TiO2 nanomaterial provided by the present invention can effectively degrade organic dyes, chlorophenol compounds, antibiotics and heavy metal ions in water under visible light conditions.
[0015] (3) The preparation process of the mixed-phase TiO2 nanomaterial provided by the present invention is simple, economical and practical, does not require special equipment and harsh conditions, has practical value, and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0017] Figure 1 is a SEM photograph of anatase TiO2 nanobelt prepared in Example 1, wherein a and b are SEM photographs at different magnifications;
[0018] Figure 2 is a SEM photograph of the TiO2 nanomaterial prepared in Comparative Example 1, wherein a and b are SEM photographs at different magnifications;
[0019] Figure 3 is a SEM photograph of the TiO2 (B) nanosheet prepared in Comparative Example 2;
[0020] Figure 4 are SEM photos of the mixed-phase TiO2 nanomaterials prepared in Examples 1, 2, and 3 of the present invention, wherein a and b are SEM photos of mNBs0.5 at different magnifications, c and d are SEM photos of mNBs1 at different magnifications, and e and f are SEM photos of mNBs2 at different magnifications;
[0021] Figure 5 XRD patterns of the mixed-phase TiO2 nanomaterials prepared in Examples 1, 2, and 3 of the present invention;
[0022] Figure 6 XRD patterns of the mixed-phase TiO2 nanomaterial prepared in Example 1 of the present invention and the NBs and NSs prepared in Comparative Examples 1 and 2;
[0023] Figure 7 is the XPS spectrum of mNBs1 prepared in Example 1 of the present invention, wherein a represents the XPS spectrum of the Ti2p orbital of the sample, and b represents the XPS spectrum of the O1s orbital of the sample mNBs1;
[0024] Figure 8 FT-IR spectra of the mixed-phase TiO2 nanomaterials prepared in Examples 1, 2, and 3 of the present invention;
[0025] Fig. 9 FT-IR spectra of the mixed-phase TiO2 nanomaterial prepared in Example 1 of the present invention and the NBs and NSs prepared in Comparative Examples 1 and 2;
[0026] Fig.10 The concentration curves of the mixed-phase TiO2 nanomaterials prepared in Examples 1, 2, and 3, the NBs prepared in Comparative Example 1, and the NSs prepared in Comparative Example 2 under ultraviolet light for photocatalytic degradation of various water pollutants, a is the degradation of methyl orange, b is the degradation of 2,4-dichlorophenol, c is the degradation of ciprofloxacin, and d is the degradation of Cr(VI);
[0027] Fig.11 The concentration curves of the mixed-phase TiO2 nanomaterials prepared in Examples 1, 2, and 3, the NBs prepared in Comparative Example 1, and the NSs prepared in Comparative Example 2 under visible light for photocatalytic degradation of various water pollutants, a for the degradation of methyl orange, b for the degradation of 2,4-dichlorophenol, c for the degradation of ciprofloxacin, and d for the degradation of Cr(VI);
[0028] Fig.12 The photocatalytic effects of the photocatalysts prepared in Example 1 of the present invention and Comparative Examples 1 and 2 on methyl orange at different pH values, where a represents pH 4, b represents pH 7, and c represents pH 10. DETAILED DESCRIPTION
[0029] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0030] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0031] A first typical embodiment of the present invention provides a mixed-phase TiO2 nanomaterial, which uses anatase phase TiO2 nanobelts as a carrier and is loaded with TiO2 (B) nanosheets.
[0032] A second typical embodiment of the present invention provides a method for preparing the above-mentioned mixed-phase TiO2 nanomaterial, comprising:
[0033] (1) dispersing titanium dioxide P25 in an alkaline solution, and then performing a solvothermal reaction, washing the precipitate after the reaction to obtain a neutral value, obtaining H2TiO3 nanobelts, and calcining to obtain anatase phase TiO2 nanobelts;
[0034] (2) Anatase TiO2 nanobelts are dispersed in a solvent, TiCl4 is added, and then a solvothermal reaction is performed to obtain a mixed phase TiO2 nanomaterial.
[0035] In one or more embodiments, in step (1), the alkali solution includes a NaOH solution;
[0036] Preferably, the concentration of the NaOH solution is 0.8 to 1.2 mol / L, preferably 1 mol / L;
[0037] Preferably, the molar ratio of titanium dioxide P25 to NaOH is 0.3-0.4:3, preferably 0.375:1.
[0038] In one or more embodiments, in step (1), the temperature of the solvothermal reaction is 200-250° C., preferably 220° C.; the time of the solvothermal reaction is 18-25 h, preferably 20 h.
[0039] In one or more embodiments, in step (1), the calcination time is 280-400° C., preferably 300° C., and the calcination time is 1.5-5 h, preferably 2 h.
[0040] In one or more embodiments, in step (2), the solvent comprises ethylene glycol.
[0041] Preferably, the concentration of anatase phase TiO2 nanobelts in ethylene glycol is 1 to 1.5 mg / mL, preferably 1.2 mg / mL.
[0042] In one or more embodiments, in step (2), the TiCl4 solution includes a TiCl4 ethanol solution, and the volume fraction of the TiCl4 ethanol solution is 8% to 15%, preferably 10%.
[0043] In one or more embodiments, in step (2), the molar ratio of anatase phase TiO2 nanobelts to TiCl4 is 1:0.5-2, preferably 1:1.
[0044] In one or more embodiments, in step (2), the temperature of the solvothermal reaction is 120-180° C., preferably 150° C.; the time of the solvothermal reaction is 8-15 h, preferably 10 h.
[0045] A third typical embodiment of the present invention provides the use of the above-mentioned mixed-phase TiO2 nanomaterial as a photocatalyst in photocatalytic degradation of pollutants.
[0046] In one or more embodiments, the pollutants include organic dyes, chlorophenol compounds, antibiotics, and heavy metal ions.
[0047] Preferably, the organic dye comprises methyl orange;
[0048] Preferably, the chlorophenol compound includes 2,4-dichlorophenol;
[0049] The antibiotics include ciprofloxacin;
[0050] The heavy metal ions include Cr(VI).
[0051] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0052] Example 1
[0053] Weigh 0.3g P25, add it to 30mL 1M NaOH solution, disperse it evenly with ultrasound, and react it at 220℃ for 20h. Wash the obtained white precipitate with HCl until the pH is neutral, and freeze-dry it to obtain H2TiO3 nanobelts. Then calcine it at 300℃ in air atmosphere for 2h to obtain one-dimensional TiO2 nanobelts. SEM photos of TiO2 nanobelts are shown in the figure. Figure 1 As shown, the TiO2 nanobelt has a regular ribbon structure and a very smooth surface, with a length of about 100nm, a width of about 10nm, and a thickness of about 1nm.
[0054] Take 30 mg of TiO2 nanobelts, add them to 25 ml of ethylene glycol, ultrasonically disperse them, evenly add 0.4 mL of 10% TiCl4 ethanol solution, stir evenly, then add 2 mL of deionized water, stir evenly, and react at 150 °C for 10 h. The obtained precipitate is centrifuged and washed alternately with water and ethanol, and dried at 70 °C to obtain a mixed phase TiO2 nanomaterial, referred to as mNBs1.
[0055] Example 2
[0056] The synthesis method of TiO2 nanobelts is the same as that in Example 1.
[0057] Take 30 mg of TiO2 nanobelts, add them to 25 ml of ethylene glycol, ultrasonically disperse them, evenly add 0.2 mL of 10% TiCl4 ethanol solution, stir evenly, then add 2 mL of deionized water, stir evenly, and react at 150 °C for 10 h. The obtained precipitate is centrifuged and washed alternately with water and ethanol, and dried at 70 °C to obtain a mixed phase TiO2 nanomaterial, referred to as mNBs0.5.
[0058] Example 3
[0059] The synthesis method of TiO2 nanobelts is the same as that in Example 1.
[0060] Take 30 mg of TiO2 nanobelts, add them to 25 ml of ethylene glycol, ultrasonically disperse them, evenly add 0.8 mL of 10% TiCl4 ethanol solution, stir evenly, then add 2 mL of deionized water, stir evenly, and react at 150 °C for 10 h. The obtained precipitate is centrifuged and washed alternately with water and ethanol, and dried at 70 °C to obtain a mixed phase TiO2 nanomaterial, referred to as mNBs2.
[0061] Comparative Example 1
[0062] The synthesis method of TiO2 nanobelts is the same as that in Example 1.
[0063] Take 30 mg of TiO2 nanobelts, add them to 25 ml of ethylene glycol, ultrasonically disperse them evenly, do not add TiCl4 ethanol solution, stir them evenly, then add 2 mL of deionized water, stir them evenly, and react at 150 °C for 10 h. The obtained precipitate is centrifuged and washed alternately with water and ethanol, and dried at 70 °C to obtain TiO2 nanomaterials, referred to as NBs. Figure 2 The SEM photo of the TiO2 nanomaterial synthesized in this comparative example. Figure 2 It can be seen that the morphology of the sample is Figure 1 The nanoribbons shown in FIG. 1 are essentially indistinguishable from those before loading the TiO2 (B) nanosheets.
[0064] Comparative Example 2
[0065] Add 0.4 mL of 10% TiCl4 ethanol solution to 25 mL of ethylene glycol and stir evenly, then add 2 mL of deionized water and stir evenly, and perform solvent thermal reaction at 150°C for 10 hours. Centrifuge the obtained precipitate, wash it alternately with water and ethanol, and dry it at 70°C to obtain TiO2(B) nanosheets, referred to as NSs. Figure 3 The SEM photo of the TiO2(B) nanosheet prepared in this comparative example shows that the TiO2(B) nanosheets form clusters with a diameter of about 100 nm, and the single sheet is an amorphous structure with a thickness of about 5 nm.
[0066] Figure 4 The SEM photos of the mixed phase TiO2 nanomaterials prepared in Examples 1, 2 and 3 of the present invention are shown in FIG. Figure 4Figures a and b are SEM images of mNBs0.5. After two steps of hydrothermal reaction, the thickness of the nanobelts increased but the 1D ribbon morphology was still intact, indicating that the NBs structure was stable and suitable as a substrate material. At this time, a small amount of TiO2 (B) nanosheets grew on the surface of the NBs. Figure 4 c and d are SEM images of mNBs1, e and f are SEM images of mNBs2. Figure 1 It can be found that with the increase of TiCl4 in the system, the TiO2 nanobelts are gradually covered by TiO2(B) nanosheets. These nanosheets grow vertically on the surface of NBs, with a close distance between the sheets and a growth direction that is basically the same as that of the TiO2 nanobelts. Figure 4 In figure e, a spherical structure assembled by some TiO2(B) was found around mNBs2, indicating that the optimal molar ratio of anatase to TiO2(B) is 1:1.
[0067] Figure 5 The XRD patterns of the mixed-phase TiO2 nanomaterials prepared in Examples 1, 2, and 3 of the present invention. The diffraction peaks at 2θ=24.8°, 27.0°, and 48.1° correspond to the anatase (101), (102), and (103) crystal planes, respectively. mNBs0.5, mNBs1, and mNBs2 all have obvious diffraction peaks with similar intensities at these positions, indicating that the nanobelt component used as the substrate is anatase phase TiO2. 2θ=27.6° corresponds to the (001) crystal plane of TiO2 (B). The diffraction peaks of mNBs0.5, mNBs1, and mNBs2 increase successively here, indicating that the loading amount of TiO2 (B) increases with the increase of TiCl4. At the same time, in the range of 2θ=10-20°, the slopes of the XRD patterns of the three samples are relatively large, which is a feature of low crystallinity and more surface defects, while the slope of NBs is relatively small in this region ( Figure 6 ), which indicates that TiO2(B) is successfully loaded on the surface of the material.
[0068] Figure 6 The XRD patterns of the mixed phase TiO2 nanomaterials prepared in Example 1 of the present invention and the NBs and NSs prepared in Comparative Examples 1 and 2 are shown in FIG. Figure 6It can be seen that mNBs1 and NBs have obvious and sharp diffraction peaks at 2θ=24.8°, 27.0° and 48.1°, indicating that the main components of NBs and mNBs1 are anatase TiO2. The characteristic peak at 2θ=27.6° corresponds to the (001) crystal plane of TiO2(B), where mNBs1 has an obvious diffraction peak, while NBs does not, indicating that the nanosheets loaded by the second step solvothermal reaction contain TiO2(B) phase. The characteristic peak intensity of NSs at 2θ=27.6° is significantly higher than that of NBs and mNBs1, indicating that the main component of NSs is TiO2(B). At the same time, there are also obvious and sharp diffraction peaks at 2θ=24.8°, 27.0° and 48.1°, indicating that the sample contains anatase phase. There are many impurity peaks in the XRD spectrum, and most of the diffraction peaks are broad, indicating that NSs has poor crystallinity, which is consistent with the characteristics of the metastable structure of TiO2(B).
[0069] Figure 7 This is the XPS spectrum of mNBs1 prepared in Example 1 of the present invention. Figure 7 a represents the Ti 2p orbital of the sample, and the characteristic peaks at binding energies of 485 and 464 eV represent Ti 4+ The low peaks at 462eV and 459eV represent the 2p 3 / 2 and 2p 1 / 2 orbitals of Ti 3+ 2p 3 / 2 and 2p 1 / 2 orbitals. It is known that the sample surface contains Ti 3+ ion. Figure 7 Figure b is the XPS spectrum of the O1s orbital of sample mNBs1. The curve can be differentiated into three sub-peaks, where Oa represents oxygen in the lattice, Ob represents oxygen defects on the crystal surface, and Oc represents oxygen molecules adsorbed on the surface of the material. Ob has a regular shape and high intensity, which indicates that there is a considerable concentration of oxygen defects on the surface of the sample. Oxygen defects can serve as active sites for surface photocatalytic reactions, and non-neutral defects can capture photogenerated carriers, promote the adsorption of materials, and separate photogenerated carriers.
[0070] Figure 8 FT-IR spectra of the mixed-phase TiO2 nanomaterials prepared in Examples 1, 2, and 3 of the present invention. In the spectra of mNBs0.5, mNBs1, and mNBs2, the wavenumbers are 500-660 cm -1 700~880cm -1 There are several obvious infrared absorption peaks in these two regions, which are caused by the vibration of Ti-O bonds in TiO2 crystals. -1The infrared absorption peak at is caused by the HO bond vibration in the hydroxyl group or adsorbed water molecules on the surface of the material. The peak intensity of mNBs0.5, mNBs1, and mNBs2 at this point gradually increases, indicating that the loading of TiO2(B) nanosheets increases the hydrophilicity of the material surface. Since there are a large number of oxygen vacancies on the sample after loading TiO2(B), the increase in surface adsorbed water means the improvement of the hydrophilicity of the sample, which is conducive to the uniform dispersion of the sample in the system during the photocatalytic reaction, thereby improving the catalytic efficiency.
[0071] Fig. 9 The XRD patterns of the mixed phase TiO2 nanomaterials prepared in Example 1 of the present invention and the NBs and NSs prepared in Comparative Examples 1 and 2 are shown in FIG. Fig. 9 It can be seen that both NBs and mNBs1 have a wave number of 500-660 cm -1 700~880cm -1 There are obvious infrared absorption peaks between them. The former is caused by the stretching vibration of Ti-O bonds in the TiO2 lattice, and the latter is caused by the bending vibration of Ti-O bonds, which proves that the main components of both are TiO2. -1 There is an obvious infrared absorption peak near the 1400 nm wavelength. This characteristic peak generally corresponds to the CO bond in the carboxyl group. This peak is formed due to the doping of a small amount of carbon atoms in the loose lattice structure of TiO2 (B). -1 and 3600cm -1 The infrared absorption peak of NSs is also slightly stronger than that of NBs. These two characteristic peaks correspond to HO bonds. As the surface area of the material increases after loading TiO2(B), more water molecules are adsorbed. Wave number of NSs is 500~660cm -1 700~880cm -1 There are obvious infrared absorption peaks between them, proving that the main component of NSs is TiO2. In the infrared spectrum of TiO2, the wave number is 1100cm -1 The infrared absorption peak at this position is unique to TiO2(B), and the infrared absorption peak of NSs at this position is significantly stronger than that of mNBs1, indicating that the sample contains a large amount of TiO2(B).
[0072] Experimental Example 1
[0073] The mixed-phase TiO2 nanomaterials prepared in Examples 1, 2, and 3 of the present invention, the NBs prepared in Comparative Example 1, and the NSs prepared in Comparative Example 2 were used as photocatalysts to catalytically degrade four common water pollutants, namely, methyl orange (MO), 2,4-dichlorophenol, ciprofloxacin (CPFX), and Cr(VI), with the concentrations of all these pollutants being 10 mg / L.
[0074] Use a 25W UV lamp as the UV light source, and a 300W Xe lamp with a filter (>400nm) as the visible light source. Weigh 10mg of the prepared photocatalyst, add it to 25ml of the target degradation product solution, and use ultrasonic treatment until it is evenly dispersed. Place the suspension in the dark and stir for 30min to reach adsorption-desorption equilibrium. Then place the suspension under a light source, take out 2mL every 2min, centrifuge and take the supernatant, use a UV-visible spectrophotometer to test the absorbance of the supernatant, then calculate the concentration according to Lambert-Beer's law, and obtain the concentration change curve of the target degradation product based on the ratio of the sampling concentration to the initial concentration.
[0075] Fig.10 The concentration curves of the mixed phase TiO2 nanomaterials prepared in Examples 1, 2, and 3, as well as the NBs prepared in Comparative Example 1 and the NSs prepared in Comparative Example 2 under ultraviolet light for photocatalytic degradation of various water pollutants. The degradation rates of mNBs0.5, mNBs1, and mNBs2 for methyl orange, 2,4-dichlorophenol, ciprofloxacin, and Cr(VI) under ultraviolet light were significantly better than those of NBs, indicating that the construction of the mixed phase significantly improved the photocatalytic performance of the TiO2 nanobelts. The photocatalytic rate and stability of mNBs1 were the best, indicating that the optimal loading ratio of anatase TiO2 nanobelts to TiO2(B) nanosheets was 1:1. Compared with the mixed phase samples, the degradation rate of NSs was lower and the trend of the decrease in pollutant concentration was closer to linear, which was because the pure TiO2(B) nanosheets had poor dispersibility in aqueous solution and could not fully contact with the degraded substances.
[0076] Fig.11 The concentration curves of the mixed phase TiO2 nanomaterials prepared in Examples 1, 2, and 3, as well as the NBs prepared in Comparative Example 1 and the NSs prepared in Comparative Example 2 under visible light for photocatalytic degradation of various water pollutants. Under visible light irradiation, mNBs0.5, mNBs1, and mNBs2 still have a relatively obvious photocatalytic effect, while the NBs composed entirely of anatase phase can hardly drive the degradation of the target substance. This shows that the introduction of TiO2 (B) improves the band structure of the material and enhances the response to visible light.
[0077] Experimental Example 2
[0078] The photocatalytic performance of the mixed-phase TiO2 nanomaterial mNBs1 prepared in Example 1, the NBs prepared in Comparative Example 1, and the NSs prepared in Comparative Example 2 were tested under acidic, neutral, and alkaline conditions, i.e., the pH value of the target degradation product solution was adjusted before the catalyst was added. Acidic conditions: The pH value was adjusted to approximately 4 using a 10% mass fraction H2SO4 solution. Alkaline conditions: The pH value was adjusted to approximately 10 using a 0.1M NaOH solution. No treatment was performed under neutral conditions. Methyl orange, which is more sensitive to pH, was selected as a reference. The photocatalytic test only used ultraviolet light as the light source, and the remaining steps were the same as those in Experimental Example 1.
[0079] Fig.12 The photocatalytic effects of the photocatalysts prepared in Example 1 of the present invention and Comparative Examples 1 and 2 on methyl orange at different pH values are shown. mNBs1 can drive photocatalytic reactions under acidic, alkaline and neutral conditions. The trend of the photocatalytic effect of NSs changing with the acidity and alkalinity of the solution is similar to that of mNBs1, but the catalytic efficiency is lower. NBs only has a photocatalytic effect under acidic and neutral conditions. This shows that the introduction of the mixed phase structure enhances the ability of TiO2 nanobelts to drive photocatalytic reactions to degrade pollutants in environments with different acidity and alkalinity.
[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A mixed phase TiO2 nanomaterial is used as a photocatalyst in photocatalytic degradation of pollutants, characterized in that: The pollutants include organic dyes; the organic dyes include methyl orange; the mixed-phase nanomaterials can be photocatalytically degraded under acidic, neutral, and alkaline conditions; The mixed phase TiO2 nanomaterial uses anatase phase TiO2 nanobelts as carriers and is loaded with TiO2 (B) nanosheets; The preparation method of the mixed phase TiO2 nanomaterial comprises: (1) Dispersing titanium dioxide P25 in an alkaline solution, and then performing a solvothermal reaction, washing the precipitate after the reaction to neutralize it, obtaining H2TiO3 nanobelts, and calcining to obtain anatase phase TiO2 nanobelts; (2) dispersing anatase TiO2 nanobelts in a solvent, adding TiCl4, and then performing a solvothermal reaction to obtain a mixed phase TiO2 nanomaterial; In step (2), the solvent includes ethylene glycol; the concentration of the anatase phase TiO2 nanobelts in ethylene glycol is 1-1.5 mg / mL; In step (2), the TiCl4 solution includes a TiCl4 ethanol solution, and the volume fraction of the TiCl4 ethanol solution is 8% to 15%; Or, in step (2), the molar ratio of anatase phase TiO2 nanobelts to TiCl4 is 1:0.5-2; In step (2), the temperature of the solvothermal reaction is 120-180°C; and the time of the solvothermal reaction is 8-15 h.
2. The use according to claim 1, characterized in that In step (1), the alkali solution includes a NaOH solution, the concentration of the NaOH solution is 0.8-1.2 mol / L; the molar ratio of titanium dioxide P25 to NaOH is 0.3-0.4:
3.
3. The use according to claim 1, characterized in that In step (1), the concentration of the NaOH solution is 1 mol / L; the molar ratio of titanium dioxide P25 to NaOH is 0.375:
1.
4. The use according to claim 1, characterized in that In step (1), the temperature of the solvothermal reaction is 200-250°C; the time of the solvothermal reaction is 18-25 h; Alternatively, in step (1), the calcination temperature is 280-400°C, and the calcination time is 1.5-5 h.
5. The use according to claim 1, characterized in that In step (1), the temperature of the solvothermal reaction is 220°C; the time of the solvothermal reaction is 20 h; Alternatively, in step (1), the calcination time is 300°C and the calcination time is 2 h.
6. The use according to claim 1, characterized in that In step (2), the concentration of anatase TiO2 nanobelts in ethylene glycol is 1.2 mg / mL.
7. The use according to claim 1, characterized in that In step (2), the volume fraction of the TiCl4 ethanol solution is 10%; Alternatively, in step (2), the molar ratio of anatase phase TiO2 nanobelts to TiCl4 is 1:
1.
8. The use according to claim 1, characterized in that In step (2), the temperature of the solvothermal reaction is 150°C; and the time of the solvothermal reaction is 10 h.
Citation Information
Patent Citations
Preparation method of pinecone-shaped TiO2 nanomaterial
CN103880072A
Preparation method of multilevel structural titanium dioxide nano flower string
CN104528820A
Preparation method of ultrathin B phase titanium dioxide nano sheet
CN105819502A
Bicrystal phase titanium dioxide nanosheet and preparation method and application thereof
CN111847504A